Mechanical Energy Recovery during Walking in Patients with Parkinson Disease - Mariangela Dipaola; E. Pavan; Andrea Cattaneo; Giuseppe Frazzitta; Gianni Pezzoli; Paolo Cavallari; C. Frigo; Ioannis U. Isaias (2016)
The mechanisms of mechanical energy recovery during gait have been thoroughly investigated in healthy subjects, but never described in patients with Parkinson disease (PD). The aim of this study was to investigate whether such mechanisms are preserved in PD patients despite an altered pattern of locomotion. We consecutively enrolled 23 PD patients (mean age 64±9 years) with bilateral symptoms (H&Y ≥II) if able to walk unassisted in medication-off condition (overnight suspension of all dopaminergic drugs). Ten healthy subjects (mean age 62±3 years) walked both at their 'preferred' and 'slow' speeds, to match the whole range of PD velocities. Kinematic data were recorded by means of an optoelectronic motion analyzer. For each stride we computed spatio-temporal parameters, time-course and range of motion (ROM) of hip, knee and ankle joint angles. We also measured kinetic (Wk), potential (Wp), total (WtotCM) energy variations and the energy recovery index (ER). Along with PD progression, we found a significant correlation of WtotCM and Wp with knee ROM and in particular with knee extension in terminal stance phase. Wk and ER were instead mainly related to gait velocity. In PD subjects, the reduction of knee ROM significantly diminished both Wp and WtotCM. Rehabilitation treatments should possibly integrate passive and active mobilization of knee to prevent a reduction of gait-related energetic components.